A NEW INSECTA, ARCHANGELSKYBLATTA VISHNIAKOVAE PINTO, GEN. NOV., SP. NOV., A PERMIAN BLATTOID FROM PATAGONIA, ARGENTINA (Ameghiniana, 2013)
A new genus and a new species of a blattoid (insecta) of the Family Archimylacridae Handlirsch, 1906, from Betancourt, Provincia de Chubut, Argentina, are described in sediments dated through the thafoflora as Lower Permian